The Relationship Of Family Support With Quality Of Life COVID-19 Patient in Hospital Inpatient Room Cibubur Family Partner in 2021 - Jamiatun, Jamiatun; Marliana, Thika; Susanti, Fajar; Nur Hartaningtyas, Sri (Journal of Ageing And Family, 2023)
Abstract: A good quality of life in COVID-19 patients is very necessary to ensure that patients are able to obtain the best health status and maintain optimal physical function or abilities. One way to improve the patient's quality of life is by providing good family support. This study aims to determine the relationship between family support and the quality of life of COVID-19 patients. This study used a cross-sectional design. Sampling used a total sampling technique with a sample size of 36 respondents. Data collection used a questionnaire. The data analysis used was univariate and bivariate analysis in the form of the chi-square test. Univariate analysis obtained showed that the majority of COVID-19 patients who were treated in inpatient rooms did not receive enough family support, namely 52.8% (19 respondents) and the quality of life of most COVID-19 patients was in the poor category, namely 58.3% (21 respondents). . The results of bivariate analysis showed that there was a relationship between family support and the quality of life of COVID-19 patients undergoing treatment in the inpatient room at Mitra Keluarga Cibubur Hospital (p=0.021). It is hoped that families can provide support and motivation to COVID-19 patients while still complying with the health protocols implemented at the hospital Keywords: Covid 19, Family Support, Quality of Life